A Delayed Diagnosis: Conflicting Investigation Results Should Be Challenged. (22nd September 2011) - Mital, D.; Desai, V.
Abstract : We present a case where a diagnosis of advanced HIV led to many other diagnoses but more importantly life-threatening multivariant Castleman's disease which is rare and was successfully treated. This case highlights the importance of questioning and challenging investigations when it does not fit with the clinical picture. Multidisciplinary teams are crucial and always seek expert advice if unsure. The much-quoted adage of "many symptoms and signs will fit one diagnosis" also bodes well in this case.